The Self-Flipped Classroom Concept: Underlying Ideas and Experiences - Vasilchenko, Anna; Cajander, Asa; Daniels, Mats; Balaam, Madeline (Proceedings - Frontiers in Education Conference, 2018)
In the modern fast changing world no formal education is able to provide learners with a complete set of knowledge, skills and competences that they would need to successfully compete on tomorrow's job market. Therefore, the role of universities is increasingly shifting towards provision of an environment where students have a chance to acquire lifelong learning skills. This paper presents underlying ideas of, and practical experiences with, an innovative pedagogy that addresses the lifelong learning skills acquisition along with additional benefits for science and technology students. The proposed approach, called self-flipped classroom (SFC), is built on a synergy of two pedagogies: learning through making and flipped classroom. To unveil the construct of the SFC, we discuss each of its components individually presenting appropriate theoretical grounding. We also report on our experiences from self-flipped classroom implementations in two countries, UK and Sweden, and in three different educational settings. From our work with the SFC concept we have identified four different roles the students can assume in a SFC scenario: creators, collaborators, communicators, and learners. We present our observations regarding the identified roles that have been found in the studied settings. We also outline some implications for teaching using the SFC concept and future research directions in this space.